2018
DOI: 10.1155/2018/2369762
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Moisture Sorption Isotherm of Crosslinked Millet Flour and Oxirane Using GAB and BET

Abstract: Epoxy resin was prepared by crosslinking epoxidized oil and millet flour. The reaction was carried out at three different temperatures (25, 40, and 55°C) and zinc chloride levels (1, 2, and 3%). Moisture sorption isotherms were determined at 0.1 to 0.9 water activity (aw) using a gravimetric sorption analyzer (Q 2000). The sigmoidal shape (type II) of the resin isotherms exhibited lower equilibrium moisture content (EMC) at higher temperature. The experimental data were modeled using GAB (Guggenheim–Anderson–d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…This leads to change in physical structure of foods. 41 These findings are consistent with the results documented by Muzaffar and Kumar 27 for tamarind pulp powder and Alamri et al 42 for millet flour.…”
Section: Discussionsupporting
confidence: 90%
“…This leads to change in physical structure of foods. 41 These findings are consistent with the results documented by Muzaffar and Kumar 27 for tamarind pulp powder and Alamri et al 42 for millet flour.…”
Section: Discussionsupporting
confidence: 90%
“…The C parameter should be a positive value which is a representation of the first layer's total heat of sorption. Therefore, a negative value is impossible (Alamri et al, 2018). A study on water sorption of Libyan date paste showed similar findings whereby the Halsey, Smith, Iglesias and Chirife, Henderson and Oswin model showed good fit to sorption data meanwhile the BET and GAB model were found to be unsuitable due to the negative value of the C parameter (Houssein, 2007).…”
Section: B Modelling Of Moisture Sorption Isothermmentioning
confidence: 89%
“…The experimental data were fitted to the GAB (Guggenheim-Anderson-de Boer) and BET (Brunauer-Emmett-Teller) isotherms models, which are the most used in food products [14].…”
Section: Objects and Methodsmentioning
confidence: 99%